The three methyls: the function and therapeutic potential of histone H3K36 trimethylation - Pfister, SX (2014)
DNA is wrapped around proteins called histones, whose modification regulates numerous cellular processes. Therefore it is not surprising that mutations in the genes that modify the histones are frequently associated with human cancer. For example, mutations in SETD2, encoding the sole enzyme that catalyses histone H3 lysine 36 trimethylation (H3K36me3), occur frequently in multiple cancer types. This identifies H3K36me3 loss as an important event in cancer development, and also as a potential therapeutic target. This thesis investigates the following questions: (1) how does the loss of H3K36me3 contribute to cancer development; and (2) what therapy can be used to kill cancers that have already lost H3K36me3. To answer the first question, this thesis shows that H3K36me3 facilitates the accurate repair of DNA double-stranded breaks (DSBs) by homologous recombination (HR). H3K36me3 promotes HR by recruiting CtIP to the site of DSBs to carry out resection, allowing the binding of HR proteins (such as RPA and RAD51) to the damage sites. Thus it is proposed that error-free HR repair within H3K36me3-decorated transcriptionally active genomic regions suppresses genetic mutations which could promote tumourigenesis. To answer the second question, this thesis reveals a clinically relevant synthetic lethal interaction between H3K36me3 loss and WEE1 inhibition. WEE1 inhibition selectively kills H3K36me3-deficient cells by inhibiting DNA replication, and subsequent fork stalling results in MUS81 endonuclease-dependent DNA damage and cell death. The mechanism is found to be synergistic depletion of RRM2 (ribonucleotide reductase small subunit), the enzyme that generates deoxyribonucleotides (dNTPs). This work reveals two pathways that regulate RRM2: one involves transcriptional activation of RRM2 by H3K36me3, and the other involves RRM2 degradation regulated by Cyclin-Dependent Kinase, CDK1 (which is controlled by WEE1, CHK1 and ATR). Based on this mechanism, the synthetic lethal interaction is expanded, from between two genes, to between two pathways. Supported by in vivo experiments, the study suggests that patients with cancers that have lost H3K36me3 could benefit from treatment with the inhibitors of WEE1, CHK1 or ATR.